Green Logistics Management Affecting Business Efficiency and Sustainable Development of SMEs in the Food Industry Sector in Thailand - Chummee, Pattarapon (Interdisciplinary Academic and Research Journal, 2025)
Background and Aims: Green logistics management refers to the concept of logistics that takes into account the impact of the transport sector and the environment on the overall process of logistics activities, including measures to reduce air pollution and gas emissions that can occur when transporting goods. Therefore, this research aims to 1) study the magnitude of the importance of each component of green logistics management, business efficiency, and sustainable development for SMEs in the food industry in Thailand, and 2) study the magnitude of the relationship between the influence between the variables of green logistics management, business efficiency, and sustainable development for SMEs in the food industry in Thailand. Methodology: The sample group was medium and small food business operators in Bangkok and its vicinity. By using the same number of observable variables as the guidelines of Hair et. al. (1995), which was 5-20 times the number of observable variables. Therefore, in this research, there were 17 observable variables multiplied by 20 times the number of variables, resulting in a sample group of 340 samples. The statistics used were confirmatory factor analysis and structural equation conceptual framework analysis. The results of the IOC test were 0.790, and the results of the reliability test were 0.894. Results: The research found that 1) the observable variable of your business continuously improving the performance of your logistics system, including methods, techniques, and tools to be competitive and maintain a sustainable market position (GL3) was the most important and 2) the relationship between the latent variable of green logistics management to the latent variable of sustainable development had the highest influence. The results of the fit index with the empirical data showed a good fit. (Chi-square=238.88, df=115, P-value=0.00, RMSEA=0.058, CFI=0.99, GFI=0.94, RMR=0.041) Conclusion: SMEs in the food industry reduce pollution during transportation, use the shortest transportation time, reduce the release of pollution into the environment to the least, implement safety and transportation tracking systems, and use information technology systems. Furthermore, products must be developed to have quality by using treatment technology or developing innovations for use in production. The technology must be environmentally friendly and able to compete internationally.